Performance of a biomass fuelled micro gas turbine power unit. - Zainal Alauddin, Zainal Alimuddin; Miskam, Muhammad Azman; Idroas, Mohd Yusof; Ali-Attab, Khalid Mohamad (Universiti Sains Malaysia, 2008)

(untitled)
Alternative fuels have been considered as a priority in the research field, especially for the renewable energy, due to the issue of fossil fuel depletion.